Experimental Verification of Current Conduction Mechanism for a Lithium Niobate Based Memristor. (30th October 2020) - Zaman, Ayesha; Subramanyam, Guru; Shin, Eunsung; Yakopcic, Chris; Taha, Tarek M.; Islam, Ahmad Ehteshamul; Ganguli, Sabyasachi; Dorsey, Donald; Roy, Ajit
Abstract : This work presents electrical characterization and analysis of the dominant charge transport mechanism suggesting inhomogeneous, filamentary conduction for a lithium niobate switching layer based memristor for use in neuromorphic computing. Memristor conductivity has been investigated both for the high and low resistance states. It is suggested that when the device is in a high resistance state, deep trap energy level within the switching layer initiate the device conduction process. The elastic trap assisted tunneling mechanism with a simple steady state approach agrees with the experimental measurements in the high resistance state. This work considers existence of inhomogeneously distributed positively charged oxygen ions/vacancies (within the oxygen deficient switching layer) as the deep trap energy level, required for electron tunneling from memristor electrode. Alternatively, ohmic conduction was found to be the main mechanism for the memristor on state conductivity at room temperature. Existence of intermediate resistive states in the memristor's high resistive region was experimentally investigated and the elastic trap assisted tunneling mechanism for such phenomena was validated through simulation.